National physical education curriculum: motor and cardiovascular health related fitness in Greek adolescents. Issue 4 (31st July 2003) - Koutedakis, Y; Bouziotas, C
Abstract : Background: State school physical education (PE) programmes are common throughout Greece. However, it is not known if the main objectives of the Greek PE curriculum are achieved. Objective: To assess the current national PE curriculum in relation to selected motor and cardiovascular health related fitness parameters. Methods: A sample of 84 Greek schoolboys (mean (SD) age 13.6 (0.3) years, height 160.7 (8.6) cm, weight 50 (10.8) kg) volunteered. Forty three indicated participation only in school PE classes and habitual free play (PE group). The remaining 41 were involved in extracurricular organised physical activities in addition to school PE and habitual free play (PE+ group). The subjects underwent anthropometric, motor (flexibility, balance, standing broad jump, hand grip, sit ups, and plate tapping), and cardiovascular health related (percentage body fat, aerobic fitness, and physical activity) fitness assessments. Results: Children in the PE group had inferior motor and cardiovascular health related fitness profiles compared with those in the PE+ group. Body fat (20.3 (8.8) v 13.9 (3.5); p<0.001), aerobic fitness (34.7 (3.7) v 43.9 (4.2); p<0.001), and time spent in intensive physical activity (0.2 (0.2) v 0.7 (0.3); p<0.001) showed the greatest differences between the two groups. In the pupils in the PE group, these were lower than the levels proposed to be necessary to combat future health risks. Adjustments for confounding variables showed a decrease in the significance of motor fitness, but not in cardiovascular health related parameters. Conclusions: The national PE curriculum for Greek secondary schools does not achieve the required levels of motor and cardiovascular health related fitness and should be reconsidered.